Interferon-free therapy of chronic hepatitis C: replacement of medications or new treatment paradigm? - S. N. Batskikh (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. A critical estimation of interferon-free modes of antiviral therapy (AVT) of chronic hepatitis C (CHC) according to the analysis of clinical studies.Key points. Interferon-free variants of CHC treatment have certain advantages over modes of interferon-α based treatment. Monotherapy by drugs with direct action on virus is less effective in comparison to combined application. Combination of agents with direct antiviral effect considerably reduces risk of resistance, increasing probability of virus eradication. The role of ribavirin at various interferon-free modes of treatment requires specification.Conclusion. New variants of the AVT providing combined application of agents with direct antiviral action (without interferon and ribavirin), will allow to simplify algorithms principally, decrease terms and improve efficacy of treatment in all categories of patients. Such variants of therapy can be considered as a new paradigm of CHC treatment.